SOSIALISASI ASI EKSLUSIF UNTUK PEMBERDAYAAN KADER POSYANDU DI DESA KEMBANGAN KABUPATEN GRESIK - Rosyana; Oktaria Pratiwi; Sumarni; Helni Putri (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2023)
Efforts to give exclusive breastfeeding have great benefits for babies in increasing immunity and as nutrition, this is because the nutritional content in breast milk contains proteins, carbohydrates, fats and minerals needed by babies in balanced amounts and plays a role in reducing infant mortality. This service was carried out in Kembangan Village, Gresik Regency for 35 PKK cadres in the form of Posyandu cadre training on Exclusive Breastfeeding and education for pregnant women about Exclusive Breastfeeding for 6 days from 11-16 February 2023. The results of the service found that most of the Posyandu cadres already understand about exclusive breastfeeding and have implemented micro teaching from cadres who attended training to pregnant women who will give birth in the 3rd trimester.